Immobilized lipase from Hypocrea pseudokoningii on hydrophobic and ionic supports: Determination of thermal and organic solvent stabilities for applications in the oleochemical industry. Issue 4 (April 2015) - Pereira, Marita Gimenez; Facchini, Fernanda Dell Antonio; Filó, Luiz Estevam Cavenage; Polizeli, Aline Moraes; Vici, Ana Cláudia; Jorge, João Atílio; Fernandez-Lorente, Glória; Pessela, Benevides Costa; Guisan, Jose Manoel; Polizeli, Maria de Lourdes Teixeira de Moraes
Graphical abstract